High treatment modification rates with lamivudine therapy in HBV-infected patients with low baseline viremia and early virological response: A multicenter study - GÜNDÜZ, FEYZA (WILEY, 2015)
ObjectiveLow baseline viremia and an early treatment response predict the best outcomes in hepatitis B virus (HBV)-infected patients treated with nucleoside analogues with low barriers to resistance. The aim of this study was to assess the long-term results and effectiveness of lamivudine in patients with low baseline viremia and early virological treatment response. MethodsIn this multicenter, real-life setting study, 111 antiviral-naive patients with low baseline viremia (HBV DNA <10(7) copies/mL) plus an early virological response (HBV DNA <300 copies/mL at week 24) treated with lamivudine were enrolled. The primary end-point was treatment failure, defined as the re-emergence of detectable viremia or at least a 1 log increase in HBV DNA, resulting in a titer of 300 copies/mL with lamivudine treatment after week 24, which required treatment modification. ResultsAltogether 111 patients, including 78 non-cirrhotic and 33 cirrhotic patients, were included in the study. Treatment failure occurred in 30.8% of the non-cirrhotic patients over a median follow-up period of 32.5 months, and the 1-, 2-, 3-, 4- and 5-year treatment failure rates were 6.5%, 14.0%, 31.4%, 39.6% and 43.1%, respectively. Treatment failure occurred in 28.8% of the whole group. There were no differences between the cirrhotic and non-cirrhotic patients. ConclusionsLamivudine treatment had a high treatment modification rate in patients with low baseline viremia and early virological response over a long-term follow-up in a real-life setting. The pretreatment and on-treatment favorable characteristics found in the studies with telbivudine appeared to be inapplicable to lamivudine.
Keywords: early response; hepatitis B virus; lamivudine; resistance; viral load; CHRONIC HEPATITIS-B; SURFACE-ANTIGEN; VIRUS-DNA; BREAKTHROUGH